Functional Outcome Measures in Acute Low Back Pain Patients in Follow up - Masud Alam, Md; Rahman, Md Mostafijur; Ali, Kh Mohammad; Hasan, Md Rakibul; Ghosh, Taposh Kumar; Alam, Md Aminul; Aziz, Md Atikul (Medicine Today, 2025)
Introduction with Objective: To assess the functional outcome measures in acute low back patients in different follow up. Materials and Methods: This observational study was carried out at the Department of Physical Medicine and Rehabilitation, Dhaka Medical College Hospital (DMCH), Dhaka from November 2021 - May 2022. All patients of acute low back pain attending the Physical Medicine and Rehabilitation department, Dhaka Medical College Hospital during study period were the study population. Purposive sampling was done according to availability of the patients. All the data were compiled and sorted properly and the quantitative data was analyzed statistically by using Statistical Package for Social Science. Result: Mean age of study population was 33.72±10.55 years with a majority of age group 16-45 years. Male predominance was found 57%. At 2 weeks, 6 weeks and 12 weeks 68.9% of the patient’s had recovered. 52.2% of patient’s noticed days off from their work initially due to low back pain and this figure reduced to 25.6% , 16.6% 8.9% at 2 weeks, 6 weeks and 12 weeks respectively. Conclusion: 31.1% of the patient’s didn’t recover from the presenting episode within 12 weeks. Medicine Today 2025, Vol.37 (1): 123-126